2017
DOI: 10.1007/s00702-017-1821-9
|View full text |Cite
|
Sign up to set email alerts
|

Dementia with Lewy bodies and Parkinson’s disease-dementia: current concepts and controversies

Abstract: Dementia with Lewy bodies (DLB) and Parkinson's disease-dementia (PDD), although sharing many clinical, neurochemical and morphological features, according to DSM-5, are two entities of major neurocognitive disorders with Lewy bodies of unknown etiology. Despite considerable clinical overlap, their diagnosis is based on an arbitrary distinction between the time of onset of motor and cognitive symptoms: dementia often preceding parkinsonism in DLB and onset of cognitive impairment after onset of motor symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
190
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(205 citation statements)
references
References 505 publications
5
190
0
10
Order By: Relevance
“…2a. This finding has been reported previously (Jellinger 2018), and supports clinical data regarding the pronounced onset of cognitive impairment in relation to extrapyramidal symptoms in DLB compared to PDD, whilst it has also been reported that striatal a-syn is increased in PDD in relation to DLB, consistent with PDD being principally a motor disorder (Tsuboi et al 2007). Furthermore, DLB cases seem to have a higher burden of Lewy bodies/neurites in limbic and neocortical regions, specifically the temporal lobe, and the CA2 region of the hippocampus compared to PDD cases ( Fig.…”
Section: Neuropathological Considerationssupporting
confidence: 90%
See 3 more Smart Citations
“…2a. This finding has been reported previously (Jellinger 2018), and supports clinical data regarding the pronounced onset of cognitive impairment in relation to extrapyramidal symptoms in DLB compared to PDD, whilst it has also been reported that striatal a-syn is increased in PDD in relation to DLB, consistent with PDD being principally a motor disorder (Tsuboi et al 2007). Furthermore, DLB cases seem to have a higher burden of Lewy bodies/neurites in limbic and neocortical regions, specifically the temporal lobe, and the CA2 region of the hippocampus compared to PDD cases ( Fig.…”
Section: Neuropathological Considerationssupporting
confidence: 90%
“…a. This finding has been reported previously (Jellinger ), and supports clinical data regarding the pronounced onset of cognitive impairment in relation to extrapyramidal symptoms in DLB compared to PDD, whilst it has also been reported that striatal α‐syn is increased in PDD in relation to DLB, consistent with PDD being principally a motor disorder (Tsuboi et al . ).…”
Section: Neuropathological Considerationssupporting
confidence: 89%
See 2 more Smart Citations
“…It is associated with an increased incidence of cognitive impairment and dementia. The pathology underlying this cognitive decline is variable: while in some patients it is purely Lewy body pathology, in many it is due to mixtures of amyloid, tau and Lewy body pathology [2]. Any therapeutic intervention to stop cognitive decline is likely to be most effective in the early stages of PD or even during prodromal stages of PD.…”
Section: Introductionmentioning
confidence: 99%